2012
DOI: 10.1590/s0004-27302012000800014
|View full text |Cite
|
Sign up to set email alerts
|

The use of fluorescence in situ hybridization in the diagnosis of hidden mosaicism: apropos of three cases of sex chromosome anomalies

Abstract: FISH has been used as a complement to classical cytogenetics in the detection of mosaicism in sex chromosome anomalies. The aim of this study is to describe three cases in which the final diagnosis could only be achieved by FISH. Case 1 was an 8-year-old 46,XY girl with normal female genitalia referred to our service because of short stature. FISH analysis of lymphocytes with probes for the X and Y centromeres identified a 45,X/46,X,idic(Y) constitution, and established the diagnosis of Turner syndrome. Case 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
5
0
7
Order By: Relevance
“…It is possible that a difference in screening methods for Y chromosome material may influence the results. Using molecular techniques such as fluorescence in situ hybridization or polymerase chain reaction, the detection of low frequency cell lines and possible structural anomalies is improved (12,13,14). Some authors reported that polymelase chain reaction is more effective than cytogenetic analysis for detecting hidden Y chromosome material (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a difference in screening methods for Y chromosome material may influence the results. Using molecular techniques such as fluorescence in situ hybridization or polymerase chain reaction, the detection of low frequency cell lines and possible structural anomalies is improved (12,13,14). Some authors reported that polymelase chain reaction is more effective than cytogenetic analysis for detecting hidden Y chromosome material (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal mosaicism is defined as the presence of two or more distinct cell lines within the same individual resulting from post-zygotic nondisjunction. When it occurs in already differentiated cells, mosaicism may be confined to one or a few tissues 26. In this context, investigation of Y-chromosome sequences in tissues of different embryonic origins is advised, such as cells of the oral mucosa, which can easily be harvested by non-invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicismo cromossômico é definido como a presença de duas ou mais linhagens celulares diferentes em um mesmo indivíduo resultante de não disjunção pós-zigótica. Quando esse ocorre em células já diferenciadas, o mosaicismo pode ser confinado a um ou poucos tecidos 26. Nesse sentido, a investigação de sequências do cromossomo Y em tecidos com diferentes origens embrionárias é aconselhada, como, por exemplo, as células de mucosa oral, que podem ser facilmente obtidas por procedimentos não invasivos.…”
Section: Discussionunclassified
“…This may explain some cases of infertility in adults with 47XYY. Indeed, the association with infertility problems was reported with scrotal findings ranging from normal to atrophic testicles, oligospermia, and varying endocrine profiles [ 3 , 8 , 10 , 31 ]. It is currently known that some cases with infertility are associated with Yq microdeletions with a significant diagnostic and prognostic value.…”
Section: Discussionmentioning
confidence: 99%